The collusive efficacy of competition clauses in Bertrand Markets with capacity-constrained retailers - Michael Trost (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2021)
We study the collusive efficacy of competition clauses (CC) such as the meeting competition clause (MCC) and the beating competition clauses (BCC) in a general framework. In contrast to previous theoretical studies, we allow for repeated interaction among the retailers and heterogeneity in their sales capacities. Besides that, the selection of the form of the CC is endogeneized. The retailers choose among a wide range of CC types - including the conventional ones such as the MCC and the BCCs with lump sum refunds. Several common statements about the collusive (in)efficacy of CCs cannot be upheld in our framework. We show that in the absence of hassle costs, MCCs might induce collusion in homogeneous markets even if they are adopted only by few retailers. If hassle and implementation costs are mild, collusion can be enforced by BCCs with lump sum refunds. Remarkably, these fundings hold for any reasonable rationing rule. However, a complete specification of all collusive CCs is in general impossible without any further reference to the underlying rationing rule.
urn:nbn:de:bsz:100-opus-19077
Keywords: L11; L13; L41; 330; Competition clauses; price-matching guarantee; price-beating guarantee; anti-competitivepractice; capacity-constrained oligopoly